(untitled) (Semiárida, 2025)
The socio-environmental crises of the 21st century reveal the limits of a scientific tradition that maintains the separation between nature and society. This dichotomy, inherited from modern thought, has fragmented knowledge production and hindered the understanding of environmental processes in their complexity. In this context, Environmental Sciences cannot be reduced to the sum of disciplines or to impact assessment techniques, but must affirm themselves as an autonomous field of knowledge. The central task is to rethink how knowledge is produced, moving beyond the supposed neutrality of “normal” science and recognizing the plurality of knowledges and values that traverse environmental conflicts. In this way, the environmental field becomes a critical space for reflection and action, where the interdependence of the social and the ecological demands specific frameworks. In conclusion, the challenge is to consolidate an environmental epistemology capable of transcending modern logics, affirming the autonomy of the field, and contributing to sustainable and habitable futures for communities and territories.